Становлення і розвиток української державності - Міжрегіональна Академія управління персоналом (My University, 2008)
У пропонованому збірнику подано статті учасників Всеукраїнської науково-практичної конференції, присвяченої найважливішій проблемі сьогодення - становленню України як держави. Розглядається формування державності в Україні у різні періоди історії та в різних аспектах. The proposed collection presents articles by participants of the All-Ukrainian Scientific and Practical Conference dedicated to the most important problem of today - the formation of Ukraine as a state. The formation of statehood in Ukraine in different periods of history and in various aspects is considered.